The importance of evaluation in the process of aid measures for people with alcoholic problem - Gluzek, Michał (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
Working with a family or a person struggling with an alcohol problem is a great challenge for services operating in this area. There is no doubt that providing such support is a process that should be subject to evaluation, which can be understood in terms of reflecting on activities that are carried out with a specific person or family, which translates into building support systems responding to the real needs of local communities regarding alcohol dependency. The considerations in the presented article are intended to encourage practitioners working with people or families with alcohol issues to deliberate on various areas of undertaken activities.